Evaluation of the Filming and Protective Properties of a New Trehalose and Ceramides Based Ingredient - Letteria Greco; Salviana Ullo; Luigi Rigano; Marco Fontana; Enzo Berardesca; Norma Cameli (Cosmetics, 2019)
The aim of this study is showing the filming and skin barrier protective properties of a new ingredient based on ceramides and trehalose and carried in lipophilic vesicles composed of lecithin and cholesterol (or phytosterols). Through an in vivo study, the restructuring and hydrating properties of this trehalose and ceramides compound have been evaluated. Furthermore, this new ingredient has been used in a topical formulation for atopic dermatitis, proving to be effective in the alterations of skin barrier. This evidence makes it an interesting ingredient for topical dermatological compositions in the treatment of dermatitis and all manifestations correlated to these skin disorders, such as edema, swelling, rash, redness, and itching. Its soothing and protective action against the painful and annoying symptoms like those given by dermatitis makes this trehalose and ceramides based ingredient for topical use.